Hubungan Tingkat Pengetahuan dan Sikap Ibu Hamil Terhadap Tanda Bahaya Kehamilan Dengan Pemanfaatan Buku KIA di TPMB Bd D Jakarta Timur - Nita Tri Wahyuni; Anes Patria Kumala; Herselowati; Annisya Yuni Sutanti (Jurnal Obstretika Scientia, 2026)
One of the government's programs to reduce MMR is by providing KIA books to every pregnant woman. The KIA book is an important communication tool for pregnant women which is equipped with information for mothers, families and the community about KIA service standards, as a tool for recognizing danger signs and early detection of maternal and child health disorders or problems. However, currently the use of KIA books in Indonesia is still low, which affects the level of knowledge and attitudes of mothers in recognizing danger signs during pregnancy, where danger signs in pregnancy are one of the factors causing high maternal and infant mortality rates. By not using the KIA book properly, it is difficult for midwives to detect danger signs of pregnancy. This study aims to determine the relationship between knowledge and attitudes of pregnant women regarding the danger signs of pregnancy with the use of KIA books at TPMB Bd D East Jakarta. The type of research used is quantitative descriptive with a crosssectional research design. The total population was 109 people, while the sample was taken based on accidental sampling by taking data on patients who were willing to become respondents with inclusion and exclusion criteria totaling 50 people. From the research results, there is a relationship between the knowledge and attitudes of pregnant women about the danger signs of pregnancy and the use of the KIA book at TPMB Bd D. Although the majority of pregnant women have used the KIA book well, overall utilization is still not optimal. Therefore, it is necessary to increase education and assistance to optimize the role of the KIA Book as a medium for information and monitoring of maternal and child health, as well as for pregnant women to receive complete information about the danger signs of pregnancy